HOW LECTURERS CONSTRUCT INTERACTIVE AND COMMUNICATIVE ACTIVITIES IN "ENGLISH FOR SPECIFIC PURPOSES" CLASSROOMS - Widya Rizky Pratiwi (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
English Lecturers are responsible for designing various teaching approaches, instruction, and efficient classroom management procedures to promote a productive atmosphere and interactive classroom experience for all, especially in English for Specific Purpose (ESP) classes. Therefore, this study aimed to explore by what methods lecturers construct interactive speaking activities in English for Specific Purpose (ESP) classes. This study used qualitative design through a case study approach. It was conducted in Politeknik Negeri Media Kreatif, Makassar Indonesia. Ten students of the Publishing study program participated in this study. First, the researcher collected the data from observations, focused group discussions, document analysis, and photographs or videos. The data were then analyzed in six stages: preparing raw data, organizing and preparing data for analysis, reading and coding data (themes or descriptions) by hand or a computer, and connecting the theme/description. The last was interpreting the meaning of the theme/description. The finding shows lecturers constructed interactive speaking activities by starting with asking the students challenging in learning English and what the students hoped in ESP for publishing course. Then the lecturer covered the ESP materials by designing various communicative and interactive activities that were categorized into three primary activities: individual presentation, paired oral performances, and group speaking practice. These activities developed the students' motivation, self-confidence, and English communicative competence.